Komitas Vardapet in the life and the poem ‘The Incessant Bell-tower’’ by Paruyr Sevak (prototype and character) - Grigoryan, Seyran (Bulletin of Yerevan University B: Philology, 2025)
The article examines the correlation between the real Komitas and the artistic character portrayed in Paruyr Sevak’s poem ‘The Incessant Bell-tower’’. The topic is relevant because readers and researchers are consistently interested in both Komitas’s biography and essence, as well as attempts to create his artistic image. The scientific novelty of the work lies in the fact that the main character of Sevak’s poem is interpreted for the first time through a detailed analysis of the facts of the real prototype’s life and work. The article is written using descriptive and psychological methods. By comparing primary sources with the text of the poem, it becomes clear that Sevak was well-acquainted with Komitas’s autobiography, scholarly works, letters, and memoirs related to him. However, Sevak used these selectively, adapting them to the needs of the lyrical-epic poem. He omitted mundane and everyday facts and emphasized the monumental, tragic, and philosophical aspects of Komitas’s essence. Through the artistic portrayal of Komitas Vardapet’s authentic biography and inner world, Paruyr Sevak directly continues and deepens the art of characterization found in Yeghishe Charents’s poem “In Memory of Komitas.” This had been discovered only a few years prior to the creation of ‘The Incessant Bell-tower’’. Partial influence can also be traced to Kostan Zaryan’s poem “To Komitas Vardapet.” At the same time, Paruyr Sevak suggests new directions for Armenian poetry and literature in terms of the artistic interpretation of the Komitas phenomenon, as well as the portrayal of prominent figures in national history and culture.